2021
DOI: 10.1017/s0272263121000383
|View full text |Cite
|
Sign up to set email alerts
|

Measurement Properties of a Standardized Elicited Imitation Test: An Integrative Data Analysis

Abstract: Elicited Imitation Tests (EITs) are commonly used in second language acquisition (SLA)/bilingualism research contexts to assess the general oral proficiency of study participants. While previous studies have provided valuable EIT construct-related validity evidence, some key gaps remain. This study uses an integrative data analysis to further probe the validity of the Korean EIT score interpretations by examining the performances of 318 Korean learners (198 second language, 79 foreign language, and 41 heritage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 54 publications
(104 reference statements)
1
7
0
Order By: Relevance
“…It is obvious that in the current landscape, there is a prevalence of studies that have centered around adult, college-level learners of English as a second language. To provide a more trustworthy and robust picture of the usefulness of EIT to assess L2 proficiency, future studies need to expand their research into other contexts and participant demographics (see Andringa & Godfroid, 2020; Plonsky, 2017; Isbell & Son, 2021). Additionally, studies that focus on target languages other than English will not only help us understand the appropriateness of elicited imitation for learners of these languages but also contribute to the research on EIT as a functional assessment instrument independent of the L2.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is obvious that in the current landscape, there is a prevalence of studies that have centered around adult, college-level learners of English as a second language. To provide a more trustworthy and robust picture of the usefulness of EIT to assess L2 proficiency, future studies need to expand their research into other contexts and participant demographics (see Andringa & Godfroid, 2020; Plonsky, 2017; Isbell & Son, 2021). Additionally, studies that focus on target languages other than English will not only help us understand the appropriateness of elicited imitation for learners of these languages but also contribute to the research on EIT as a functional assessment instrument independent of the L2.…”
Section: Discussionmentioning
confidence: 99%
“…To bolster the validity argument for EIT as a trustworthy measure of L2 proficiency, L2 research has largely focused on examining the relationship between learners’ performance on EI tasks and more established measures of proficiency. Several EIT validation studies found significant positive correlations between learners’ EIT scores and scores on standardized proficiency measures with correlations ranging from 0.62 for IELTS (Erlam, 2006) to 0.76 for Test of Proficiency in Korean (TOPIK) (Kim et al, 2016; see also Isbell & Son, 2021). Similarly, strong and positive correlations from r = 0.87 to 0.91 have been found between EIT and Simulated Oral Proficiency Interviews (SOPI), particularly in L2 Spanish (Bowden, 2016; Ortega, 2000; Ortega et al, 2002).…”
Section: Eit As a Measure Of L2 Proficiencymentioning
confidence: 99%
“…In another kind of activity, researchers are beginning to conduct integrative data analyses-pooling related data collected by the same elicitation technique though not synchronously. Although not a new concept (Bauer & Hussong, 2009), it has rarely been used in the language sciences (cf., Isbell & Son, 2022). Bringing these endeavors together, we envisage freely available and accessible data collection tools (such as measures of individual differences) that output full datasets to facilitate the large-scale accumulation of ethically compliant open datasets that are tagged with metadata and analyzable by those who did not collect the data.…”
Section: Envisioning Ways Forward For Open Materialsmentioning
confidence: 99%
“…In another kind of activity, researchers are beginning to conduct integrative data analyses -pooling related data collected by the same elicitation technique though not synchronously. Although not a new concept (Bauer & Hussong, 2009), it has rarely been used in the language sciences (cf., Isbell & Son, 2022). Bringing these endeavours together, we envisage freely available and accessible data collection tools (such as measures of individual differences) that output full datasets to facilitate the large-scale accumulation of ethically-compliant open datasets that are tagged with metadata and analysable by those who did not collect the data.…”
Section: Envisioning Ways Forward For Open Materialsmentioning
confidence: 99%